PERMINTAAN AIR BERSIH KOTA PEKANBARU (Studi Kasus Pada PDAM Tirta Siak) - Yovi Ananda Saputra; Rita Yani Iyan; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the Clean Water Demand in PDAM Tirta Siak Pekanbaru. This research was conducted in a period of one year ie 2015.This study used multiple linear regression analysis. Partial testing using t-statistics and tests simultaneously using F-statistics. It also performed classical assumption, that all of these tests using a tool SPSS 21.The results showed that household income amounted to 0,293%. What this means is that any increase household incomes by 1 degree will increase demand for clean water for 0,293% assuming other variables remain. Amounted to 1,031% household members. What this means is that any increase in household members by 1 degree will increase demand for clean water for 1,031% assuming other variables remain while the water tariff of - 0.034%. What this means is that any increase in water rates by 1 degree will reduce the demand for clean water for 0,034% assuming other variables remain. Unknown value of R Square of 0.655. What this means is that the contribution of the influence of the independent variable on the dependent variable is equal to 65.5%. While the remaining 34.5% is influenced by other variables yan is not included in this regression model.While most dominant variable among the three variables in this study are variable (X2) the number of household members 0627% in view of Standardized Coefficients Beta of three variables turned out to be the most dominant X2.Keywords: Income, Family Members,Tariff and Water Demand